Population dynamics of grey mackerel fish (Thunnus tonggol) caught in fishery management areas (WPP 711) - Hadinata, Fitra Wira; Ahmad, Mulyadi; Utami, Pratita Budi (Universitas Malikussaleh, 2024)
Grey mackerel is a fish that originates from tropical and subtropical waters worldwide. This pelagic fish has very important economic value in the Indonesian fishing industry. Grey mackerel production in WPP 711 using gillnet fishing gear has shown a fluctuating trend in recent years. This research is to estimate the stock of grey mackerel fish caught by fishermen who landed at PPN Pemangkat and Sungai Rengas Fishing Port. This research uses two data collection methods, namely primary and secondary data collection. The results of data analysis of the relationship between length and weight in the catch of grey tuna fish of 1,015 total fish samples produced the equation W = 0.0929x2.5504 (r2 = 0.8764) with a value of 0.0929 and the b value of 2,5504. Based on the results of the t-test, it shows that the value of b < 3 in the growth pattern is negative allometric, meaning that the relationship between length and weight has a slow and rapid increase in weight compared to the increase in length. The landed grey mackerel had a growth rate coefficient (K) = 0.40. Tuna fish obtained a total mortality value (Z) of 1.81/ year. The exploitation rate (E) of grey tuna caught is 0.28/ year, which means the exploitation rate is still relatively low.Keywords: Gray mackerel; Pelagic Fish; Population dynamics; WPP 711Grey mackerel is a fish that originates from tropical and subtropical waters worldwide. This pelagic fish has very important economic value in the Indonesian fishing industry. Grey mackerel production in WPP 711 using gillnet fishing gear has shown a fluctuating trend in recent years. This research is to estimate the stock of grey mackerel fish caught by fishermen who landed at PPN Pemangkat and Sungai Rengas Fishing Port. This research uses two data collection methods, namely primary and secondary data collection. The results of data analysis of the relationship between length and weight in the catch of grey tuna fish of 1,015 total fish samples produced the equation W = 0.0929x2.5504 (r2 = 0.8764) with a value of 0.0929 and the b value of 2,5504. Based on the results of the t-test, it shows that the value of b < 3 in the growth pattern is negative allometric, meaning that the relationship between length and weight has a slow and rapid increase in weight compared to the increase in length. The landed grey mackerel had a growth rate coefficient (K) = 0.40. Tuna fish obtained a total mortality value (Z) of 1.81/ year. The exploitation rate (E) of grey tuna caught is 0.28/ year, which means the exploitation rate is still relatively low. Keywords: Gray mackerel; Pelagic Fish; Population dynamics; WPP 711